Cystatin B Involvement in Synapse Physiology of Rodent Brains and Human Cerebral Organoids - Penna, Eduardo; Cerciello, Angela; Chambery, Angela; Russo, Rosita; Cernilogar, Filippo M.; Pedone, Emilia Maria; Perrone-Capano, Carla; Cappello, Silvia; Di Giaimo, Rossella; Crispino, Marianna (Frontiers in Molecular Neuroscience, 2019)
Cystatin B (CSTB) is a ubiquitous protein belonging to a superfamily of protease inhibitors. CSTB may play critical role in brain physiology because its mutations cause progressive myoclonic epilepsy-1A (EPM1A), the most common form of progressive myoclonic epilepsy. However, the molecular mechanisms underlying the role of CSTB role in the Central Nervous System (CNS) are largely unknown. To investigate the possible involvement of CSTB in the synaptic plasticity, we analyzed its expression in synaptosomes as model system in studying the physiology of the synaptic regions of the CNS. We found that CSTB is not only present in the synaptosomes isolated from rat and mouse brain cortex, but also secreted into the medium in a depolarization-controlled manner. In addition, using BONCAT (biorthogonal noncanonical amino acid tagging) procedure, we demonstrated, for the first time, that CSTB is locally synthesized in the synaptosomes. The synaptic localization of CSTB was confirmed in a human 3D model of cortical development, namely cerebral organoids. Altogether these results suggest that CSTB may play a role in the brain plasticity and open a new perspective in studying the involvement of CSTB deregulation in neurodegenerative and neuropsychiatric diseases.